Honorifik Bahasa Korea dan Bahasa Indonesia - Iva Hanani (Universitas Gadjah Mada, 2022)
The aim of this study is to describe the Korean and Indonesian honorifics and compare the honorifics of the two languages. This research is a qualitative research using a contrastive analysis method. Data in the Korean language is collected from the author's private messages with Korean, and data in Indonesian is collected from examples in the referenced literature and substituted with words from the same word class. Based on the analysis that has been carried out, Korean and Indonesian honorifics are both grammatically and lexically realized. However, the grammatical elements that make up Korean honorifics are not limited to one type of sentence, while in Indonesian it is only used in imperative sentences. Vocabularies that contain honorific meanings in Korean are found in adjectives, verbs, and personal pronouns, while in Indonesian mostly are found in personal pronouns and only a few in words from other word classes. From the point of view of Korean honorifics, Indonesian honorifics can be classified into hearer honorifics. In addition, the Indonesian language has subject honorifics, either directly or indirectly, which are lexically realized.